Institutional Economics : Its Place in Political Economy, Volume 1 - Sebesta, Sam (London : Taylor and Francis, 2017)
"Commons opened Institutional Economics by declaring: ""My point of view is based on my participation in collective activities, from which I here derive a theory of the part played by collective action in control of individual action."" This sentence well summarizes the three key elements of this book--its theoretical intent, the importance Commons gave to his own experience in institutional reform in shaping these ideas, and the focus on the concept of the institution as a collective constraint on individual action."--Provided by publisher.
Chapter I The Point of View / John R. Commons -- chapter II Method / I. John Locke -- chapter III Quesnay / John R. Commons -- chapter IV Hume and Peirce / John R. Commons -- chapter V Adam Smith / John R. Commons -- chapter VI Bentham Versus Blackstone / John R. Commons -- chapter VII Malthus / John R. Commons -- chapter VIII Efficiency and Scarcity / John R. Commons -- chapter IX Futurity / John R. Commons.
OCLC-licensed vendor bibliographic record.
Keywords: Institutional economics